Multinetwork vitrimer for high-temperature polymer electrolyte membranes - Yang, Seonghyeon; Kim, Eunjong; Choi, Junseok; Choi, Yong-Seok; Kim, Sung-Kon (Elsevier BV, 2025)
In this study, multinetwork polymer electrolyte membranes (MNPEMs) featuring three chemical bonds including associative dynamic covalent bond, pyrophosphate, and hydrogen bond are created for the use in high-temperature polymer electrolyte membranes (HT-PEMs). The three types of bonds in MNPEMs vary depending on the ratio of monomeric phosphoric acid (PA) to soft and hard epoxies. When the molar ratio of PA to epoxies is 3:1, both the mechanical property (toughness similar to 3.4 MPa) and proton conductivity (2.0 mS cm(-1) at 150 degrees C under anhydrous conditions) are observed to reach their maximum values simultaneously. Note that PA, that is typically used as proton-conducting medium in HT-PEMs, cannot leach out during cell operation, because PA is a monomer for MNPEMs, not an additional dopant in this study, potentially ensuring long-term stability in high-temperature fuel cell operation. MNPEMs also show exceptional thermal stability, and the ability to form a protective char layer at high temperatures, contributing to their fire-retardant properties. Furthermore, they possess self-healing capabilities due to beta-hydroxyl phosphate ester exchange reactions, with an activation energy of 88 kJ mol(-1), enhancing its resilience against potential mechanical damage during fuel cell operation. These findings suggest that MNPEM is a promising candidate for use in HT-PEMs.